Autocrine Acetylcholine, Induced by IL-17A via NFκB and ERK1/2 Pathway Activation, Promotes MUC5AC and IL-8 Synthesis in Bronchial Epithelial Cells - Angela Marina Montalbano; Giusy Daniela Albano; Anna Bonanno; Loredana Riccobono; Caterina Di Sano; Maria Ferraro; Liboria Siena; Giulia Anzalone; Rosalia Gagliardo; Michael Paul Pieper; Mark Gjomarkaj; Mirella Profita (Mediators of Inflammation)
IL-17A is overexpressed in the lung during acute neutrophilic inflammation. Acetylcholine (ACh) increases IL-8 and Muc5AC production in airway epithelial cells. We aimed to characterize the involvement of nonneuronal components of cholinergic system on IL-8 and Muc5AC production in bronchial epithelial cells stimulated with IL-17A. Bronchial epithelial cells were stimulated with recombinant human IL-17A (rhIL-17A) to evaluate the ChAT expression, the ACh binding and production, the IL-8 release, and the Muc5AC production. Furthermore, the effectiveness of PD098,059 (inhibitor of MAPKK activation), Bay11-7082 (inhibitor of IkBα phosphorylation), Hemicholinium-3 (HCh-3) (choline uptake blocker), and Tiotropium bromide (Spiriva®) (anticholinergic drug) was tested in our in vitro model. We showed that rhIL-17A increased the expression of ChAT, the levels of ACh binding and production, and the IL-8 and Muc5AC production in stimulated bronchial epithelial cells compared with untreated cells. The pretreatment of the cells with PD098,059 and Bay11-7082 decreased the ChAT expression and the ACh production/binding, while HCh-3 and Tiotropium decreased the IL-8 and Muc5AC synthesis in bronchial epithelial cells stimulated with rhIL-17A. IL-17A is involved in the IL-8 and Muc5AC production promoting, via NFκB and ERK1/2 pathway activation, the synthesis of ChAT, and the related activity of autocrine ACh in bronchial epithelial cells.